BUILDING ENVIRONMENTAL AWARENESS THROUGH MINI GARDENS AND RECYCLING OF CHILDREN'S WASTE IN RA AL-KHOIRIYAH - Indasah, Indah (Ngejha, 2025)
Environmental awareness in early childhood is important because it helps instill a sense of love and responsibility for nature from an early age, forms a character that cares about the environment until adulthood, and becomes the foundation for the creation of a more sustainable future. By instilling this awareness, children will better understand the importance of maintaining the cleanliness and sustainability of the surrounding environment. Children play an important role in shaping a generation that cares about environmental sustainability. At an early age, their curiosity is very high and they tend to absorb information quickly. This is the right time to introduce the values of caring for nature and how they can play a role in protecting it. Instilling a sense of responsibility from a young age is very important so that children get used to doing simple things that have a positive impact on the environment. When they understand why taking care of nature is important, they will be motivated to act, even from small things. In addition, good habits such as throwing garbage in its place, saving water, and using energy wisely should also be formed early. This habit will become part of their lifestyle until adulthood and also support environmental conservation efforts.